Social Entrepreneurship on Gen Z Students - Tsabita Khwarazmita (Journal of Career and Entrepreneurship, 2022)
This study aims to reveal the dimensions that can influence social entrepreneurial intentions in Generation Z students. This study re-examines the usefulness of social entrepreneurship dimensions by earlier studies, such as innovation, proactiveness, and risk-taking with diverse objects. Using a population of 1500 from 2018-2020 private students who are contained in generation Z. The sampling technique utilized is convenience sampling with a sample of 98 people. Processing of data using SmartPLS 4.0. The results of data processing indicate that in this subject innovation and risk-taking have a significant effect on the social entrepreneurial intention of generation Z. Meanwhile, there is no proactive effect on the social entrepreneurial intention of generation Z.